Association between prenatal maternal sleep quality, neonatal uncinate fasciculus white matter, and infant negative emotionalityResearch in context - Melissa Nevarez-Brewster; Catherine H. Demers; LillyBelle K. Deer; Özlü Aran; Robert J. Gallop; Mercedes Hoeflich Haase; Khalid Al-Ali; Maria M. Bagonis; John H. Gilmore; M. Camille Hoffman; Martin A. Styner; Benjamin L. Hankin; et al. (EBioMedicine)
Summary: Background: Poor prenatal maternal sleep is a pervasive, yet modifiable, health concern affecting maternal and foetal wellbeing. Experimental rodent studies demonstrate that prenatal maternal sleep deprivation affects offspring brain development and leads to adverse outcomes, including increased anxiety-like behaviour. We examined the relation between prenatal maternal sleep quality and neonatal white matter development and subsequent infant negative emotionality. Methods: Participants included 116 mother-infant (53% female) dyads. Prenatal sleep quality was prospectively assessed three times during gestation (16, 29, and 35 gestational weeks) using the Pittsburgh Sleep Quality Index. Neonatal white matter, as indexed by fractional anisotropy (FA), was assessed via diffusion weighted magnetic resonance imaging. Negative emotionality was measured via behavioural observation and maternal report when the infant was 6-months of age. Findings: More prenatal sleep problems across pregnancy were associated with higher neonatal FA in the uncinate fasciculus (left: b = 0.20, p = .004; right: b = 0.15, p = .027). Higher neonatal uncinate FA was linked to infant negative emotionality, and uncinate FA partially mediated the association between prenatal maternal sleep and behavioural observation of infant negative emotionality. Interpretation: Findings highlight prenatal sleep as an environmental signal that affects the developing neonatal brain and later infant negative emotionality. Funding: National Institutes of Health (R01MH109662, R01HL155744, P50HD103573, K12AR084226, F32 Training fellowships MH125572, HL165844, MH106440, and diversity supplement R01HL155744-01S1).